Behavioral Pattern in the United States in the Face of Upheavals of Arab Countries - Sabeti, Seyed Moayed; Moghaghenia, Hamed (Journal of History Culture and Art Research, 2017)
Conditions and upheavals, by their characteristics, including people opposition with governments and alteration in regional order, have challenged the US strategic interests in the Middle East region and forced the authorities of Washington to manage and strategize upheavals. The type of US encounter with the trend of upheavals, approach of the ruling regime, the future of people movement and available alternative, interests, and security of Israel and contradiction between strategic interests and democratic principles were amongst the most important issues facing the United States. The present article is seeking to find the answer to this question that what sort of relationship does exist between United States policies in the Middle East from one hand and recent upheavals in Arab countries on the other hand? The assumption of the article is that in the past two decades the one sided role of the US in forming the upheavals of Middle East has changed into a bilateral relationship and the behavior of this country in the process of recent upheavals, affected by the presence of the people of Arab countries in internal politics of their own country in numerous cases has changed into a reaction behavior. Finally, it should be said that contrasts between society and government in Arabic Middle East, is considered as one of the prominent challenges of the US in decision-making process and management of region unrests. On the other hand, the lack of a specified instruction and strategy by Americans is another problem of the US in this region.